Le lesioni del legamento crociato anteriore del ginocchio del paziente in accrescimento - Memeo, A.; Pedretti, L.; D'Amato, D.; Trezza, P. (Lo Scalpello - Journal, 2018)
ACL LESIONS IN SKELETALLY IMMATURE PATIENTSACL injuries in prepubescent patients are being seen with increasing frequency. The reasons include intensive yearround training regimens and early sport specialisation, but also a more precise diagnosis of the trauma and its causes.The traditional treatment was conservative, but with poor outcomes and an high rate of chondral and articulardamages caused by prolonged instability. As a result, there is the need for surgical anterior cruciate reconstructioneven in skeletally immature patients. Many surgical techniques have been described to achieve a physeal sparingreconstruction, thus avoiding iatrogenic damages of the limb growth. The proposed techniques can be divide into threegroups: extra-epiphyseal, trans-epiphyseal and all-epiphyseal. Some issues are related to the non-anatomicalstabilisation achieved with the extra-epiphyseal reconstruction. All-epiphyseal reconstruction, which involves sometechnical complexities, should be preferred in younger patients with fully open physes. The trans-epiphyseal approachhas shown satisfactory outcomes in patients with older skeletal age, reducing the surgical impact on growth cartilageswith some technical adjustments if compared with the usual technique for adults.